The management coach - Slater, Rus (London : Hodder & Stoughton, 2014)
By the end of this book you will be a better manager than you are now - Understand your strengths and weaknesses - Set and manage your goals - Understand your team - Work better with your own boss - Improve your business Other books help you talk the talk. The Teach Yourself Coach books helps you walk the walk.
Includes index.
Keywords: Management; Gestion; management; Management